Nuevas aproximaciones para la comprensión del militarismo uruguayo a través de un análisis social - Manuel TALAMANTE PEREZ (Caravelle)
Contributions in Latin American historiography to the theme of militarism have been very recurring in recent years. And although Lorenzo Latorre’s period is known, it has not been approached through the support group of Uruguayan militarism. That is why this article aims to fill that gap and publicize the social basis that supported militarism during a part of the process of economic modernization enabling the State to consolidate its power. To carry out this analysis, we will start by a prosopographic study of the social support group to Lorenzo Latorre and the new possibilities that this methodology provides.